Does Women Empowerment Predict Contraceptive Use? A Study in a Rural Area of Hooghly District, West Bengal - Dasgupta, Aparajita Dasgupta; Bandyopadhyay, Kajari; Bandyopadhyay, Lina; Paul, Bobby; Banerjee, Sitikantha (Indian Journal of Community Health, 2016)
Background: India launched the world’s first national family planning programme in 1952. Unfortunately, considerable numbers of eligible couples in India are still not using any method of contraception in spite of the fact that knowledge related to contraceptives are not lacking. Studies reported that the status of the women in the family and largely in the community, represented by a measure ‘women empowerment’ plays a role in determining contraceptive use. However, there is dearth of literature in this regards especially among women of reproductive age of West Bengal. Aims & Objectives: To find out the current contraceptive use and its relationship, if any with women empowerment among adult married women of reproductive age group in a rural area of West Bengal. Material & Methods: Community based cross-sectional study was conducted among 151 WRA using interviewer-administered questionnaire. Current use of contraceptive was the outcome variable. The main explanatory variable was ‘empowerment score’-a summed measure of four domains: ‘financial autonomy’, ‘freedom of movement’, ‘involvement in household level decision making’ and ‘woman’s power in sexual and reproductive decision making’. Results: 63.6% study participants were using any method of contraception at the time of study. Women empowerment [AOR (CI): 1.11 (1.02-1.22)] and education of women [AOR (CI): 2.56 (1.13-5.85)] were significantly associated with contraceptive use, even after adjustment with other independent variables. Conclusion: Educating women and empowering them will improve the family planning practices. This will, in long run play a pivotal role in improving family and community health.